EXPERIMENTS ON THE CONVERSION OF TYPHUS STRAINS - VARELA, GERARDO; PILZ, H; MOOSER, HERMANN (INSTITUTO DE HIGIENE, POPOTLA, CD. MEXICO DF, MEX, 1949)
Two types of strains of typhus virus are observed in Mexico: first the murine type which is obtained from wild rats in nature, from isolated endemic cases, and from cases during short epidemic outbreaks, and second, the epidemic type of strains which is o
J EXP MED
Keywords: EXPERIMENTS, CONVERSION, TYPHUS; CIENCIAS MEDICAS; PATOLOGIA; TIFO